Sociodemographic Characteristics, Dietary Practices, and Nutritional Status of Adults with Hypertension in a Semi-Rural Community in the Eastern Region of Ghana - Esi K. Colecraft; Matilda Asante; Aaron K. Christian; Seth Adu-Afarwuah (International Journal of Hypertension)
Introduction. Hypertension is a major contributor to the global disease burden and mortality. Evidence suggests increasing hypertension prevalence in Ghana but there is limited public awareness and information on the characteristics of those with the disease. Objective. To describe the baseline characteristics of adults with hypertension who were randomized to receive either hypertension related nutrition education plus hospital-based standard of care or only the standard of care (control group) in Asesewa, a semi-rural community in the Eastern Region of Ghana. Only baseline data were used in the present analysis. Methods. A cross-sectional baseline survey was completed for 63 adults with confirmed hypertension diagnosis. Data on sociodemographic characteristics and diet were obtained through interviews and participants’ body mass index (BMI) was computed. Pearson chi-square statistic was used to assess differences between those with both elevated diastolic blood pressure (DBP) and systolic blood pressure (SBP) and those with only elevated SBP. Results. Mean ± SD age of participants was 54.5±13.8 years. Approximately 71% of participants had both elevated SBP (>140 mmHg) and DBP (>90 mmHg) while the remaining 29% had only elevated SBP. The median number of times the food groups beneficial to hypertension management were consumed in the preceding week to the interview was 1 for green leafy vegetables, 1 for dairy products, 2 for fruits, and 4 for legumes. The median number of times for consuming harmful food groups was 3 for salted fish and 7 times for fats and oils. Signifcantly more participants in the age group above 50 than the younger participants had elevated SBP (83.3 vs. 16.7:P=0.027) and those with BMI equal to or greater than 25 were more likely to have both elevated SBP and DBP (P=0.047). Conclusions. Findings from this study have implications for the prevention and management of hypertension in this semi-rural population.